Addressing Information Needs to Reduce the Audit Expectation Gap: Evidence from Dutch Bankers, Audited Companies and Auditors. (28th May 2015) - Litjens, Robin; van Buuren, Joost; Vergoossen, Ruud
<x xml:space="preserve">Abstract</x> This study examines what the impact is of frequently proposed information needs on reducing the audit expectations gap (AEG), including information about the audited company, information about the audit process and changes to the auditors' report. We base our findings on a survey of 302 participants from the Netherlands, consisting of 61 bankers, 118 preparers and 123 auditors. We consider the AEG in essence to be a classic agency problem. We find that stakeholders fall back in basic strategies to maximize their own value: bankers require additional information, management is reluctant to let the auditor provide sensitive information and auditors try to minimize their risks. Further, we observe that only information about the audit process with respect to continuity and the reporting of errors in the financial statements may reduce the bankers' AEG. Finally, we observe that format changes to the auditors' report do not reduce the bankers' AEG.